The Role of Public Policy in Fostering Technological Innovation and Sustainability - Mahardhani, Ardhana Januar (PT. LITERASI SAINS NUSANTARA, 2023)
In this modern era, technological innovation has become one of the main keys in improving the efficiency, productivity, and competitiveness of a nation. On the other hand, awareness of the importance of environmental sustainability is increasing, given challenges such as climate change, natural resource depletion, and the negative impacts of pollution. The purpose of this research is to analyse the role of public policy in promoting technological innovation and sustainability. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that the role of public policy in encouraging technological innovation and sustainability is very important in achieving a sustainable and advanced future. The right policies can create an enabling environment for innovation, stimulate research and development, and empower human resources to face rapid technological challenges.